Performance evaluation of buffering strategies in ATM network - 241845 Kaswan Yusoff (Kuala Lumpur : UTM, 1994)
High Speed packet switched networks such as B-ISDN required algorithms to manage the flow of traffic into and through the network. End-to-end congestion control algorithms will do much to ensure that over-load periods are minimized, but intelligent buffering decisions are internal nodes may aid in managing congestion by shifting cell loss to lower priority traffic. This project describe a simulation study of two space priority queueing algorithms under realistic traffic models, and show their performance of these algorithms depends on the shape and the type of traffic.